2005
DOI: 10.1097/01.hjh.0000186023.74245.48
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, antihypertensives and mutations in the Von Hippel–Lindau gene in renal cell carcinoma: results from the Netherlands Cohort Study

Abstract: In this study non-significantly increased risks for history of hypertension and use of antihypertensive medication with RCC were observed. The association with hypertension was stronger in RCC patients with VHL mutations, while there was a positive association of diuretics use and risk of RCC without VHL mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
24
0
2
Order By: Relevance
“…In two prospective studies, antihypertensive treatment was associated with higher risk of renal cell cancer (Fraser et al, 1990;Heath et al, 1997), but others found no association (Grove et al, 1991;Flaherty et al, 2005;Schouten et al, 2005). One large study linking prescriptions and cancer registration in Denmark indicated that antihypertensive medication may increase risk, but was interpreted as being due to confounding by underlying hypertension (Fryzek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two prospective studies, antihypertensive treatment was associated with higher risk of renal cell cancer (Fraser et al, 1990;Heath et al, 1997), but others found no association (Grove et al, 1991;Flaherty et al, 2005;Schouten et al, 2005). One large study linking prescriptions and cancer registration in Denmark indicated that antihypertensive medication may increase risk, but was interpreted as being due to confounding by underlying hypertension (Fryzek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In men, there was no association with blood pressure. The association of blood pressure with risk of renal cell cancer has been investigated in a number of cohort (Fraser et al, 1990;Grove et al, 1991;Coughlin et al, 1997;Heath et al, 1997;Chow et al, 2000;Choi et al, 2005;Flaherty et al, 2005;Fryzek et al, 2005;Lindgren et al, 2005;Schouten et al, 2005) and case -control (McLaughlin et al, 1995;Yuan et al, 1998;Shapiro et al, 1999) studies, using as principal exposure variable either recorded blood pressure or reported hypertension. In men, recorded blood pressure has shown a convincing exposure -response gradient related to renal cell cancer risk (Coughlin et al, 1997;Chow et al, 2000).…”
mentioning
confidence: 99%
“…Cigarette smoking was associated with renal cell cancer risk for men but not specifically with VHL gene mutations, irrespective of sex, suggesting that smoking may cause renal cell cancer independent of VHL gene mutations (58). With respect to hypertension and use of antihypertensive medications, the association of hypertension was stronger in renal cell cancer cases with VHL gene mutations, whereas use of diuretics was associated with renal cell cancer without VHL gene mutations (59). Results were suggestive of higher relative risks for wildtype VHL tumors with a-carotene, h-cryptoxanthin, folate, and supplemental vitamin C and multivitamin intake (60).…”
Section: Discussionmentioning
confidence: 92%
“…103 Several [55][56][57]63,106 cohort studies have demonstrated an increased risk even after exclusion of the early years of follow-up, when early stage, prediagnostic renal tumors may themselves lead to elevated blood pressure. Recent fi ndings from the Netherlands cohort study 105 suggest that the association with hypertension may be stronger among the small fraction of sporadic renal cell cancer patients with von Hippel-Lindau gene mutations, but this needs to be confi rmed in future studies.…”
Section: Hypertension and Antihypertensive Medicationsmentioning
confidence: 97%
“…101,102 While it is diffi cult to separate the effects of hypertension or its treatment on renal cell cancer risk, as they are highly correlated variables, the collective epidemiologic evidence to date suggests that it is hypertension itself that is the determinant. Most studies have reported risks for renal cell cancer associated with either recorded blood pressure or reported hypertension ranging between 1.2 and 2 or greater, 48,51,[54][55][56]62,68,69,72,[103][104][105][106] although not all of the studies were able to adjust for the effect of antihypertensive medications. Dose-response relations between measured blood pressure level and renal cell cancer risk have been reported, 54,56,106 although only one of these studies provided data on women and considered the effect of antihypertensive medication.…”
Section: Hypertension and Antihypertensive Medicationsmentioning
confidence: 99%